Keragaman dan Kelimpahan Artropoda Tajuk Tanaman Cabai dan Terong di Pringsewu Lampung - Swibawa, I Gede; Oktavia, Tiara; Rahma Dhona, Alfira; M Hariri, Agus; Efri, Efri (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Swibawa IG, Oktavia T, Dhona AR, Hariri AM, Efri E. 2022. Diversity and abundance of arthropods on canopy of chili and eggplant crops in Pringsewu, Lampung. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 154-165. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Chili and eggplant were two famous vegetable crops in Pringsewu Lampung and their cultivation practice were intensively using synthetic mulch, inorganic fertilizer, and synthetic pesticides, that may affect to arthropods communities. The purpose of this research was to study diversity and abundance of arthropod community inhabited canopy crop of chili and eggplant in Pringsewu, Lampung. Sampling of arthropods by yellow sticky trap and ground cloth methods on 4, 6, and 10 weeks after planting of chili and eggplant crops were conducted in district of Adiluwih, Pringsewu, province of Lampung on May until August 2022. Identification of arthropods into taxon of family was done in Plant Pest Laboratory, University of Lampung. The result show that the abundance of arthropod that indicated by total individual that were caught were 905 on Chili and 1399 on eggplant respectively. Taxonomic diversity of arthropod on chili were 8 order, 34 families with Shannon index of 2.38 and Simpsons Index of 0.84, while on eggplant were 8 order and 32 families with Shannon Index of 2.58 and Simpsons Index of 0.89. The functional groups of arthropods on Chili consisted of 14 families of herbivore and 20 families of non-herbivore, while on eggplant there were 14 families of herbivore and 18 families of non-herbivore arthropods. Base on Sorenson Index, the similarities of arthropods communities on chili and eggplant was 0.76. Diversity and abundance of arthropods both on chili and eggplant was higher on 6 than 4 and 10 weeks after planting crop old. Total individual of herbivore arthropods was higher than non-herbivore.